2022
DOI: 10.1155/2022/2948248
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase 4 Is a Predictor of Diabetic Kidney Disease Progression in Type 2 Diabetes Mellitus

Abstract: Background. Diabetic kidney disease (DKD) represents a heavy burden in type 2 diabetes mellitus (T2DM). Ferroptosis plays an important role in DKD, and it thus provides new perspectives to pursue more related biomarkers to assess the disease severity and prognosis. Glutathione peroxidase 4 (GPX4) is the mainstay in regulating ferroptosis. The current study investigated the predictive value of kidney GPX4 expression level in DKD progression. Methods. We measured GPX4 levels in kidney paraffin sections of 85 bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…24 Wang et al showed that in T2DM patients Gpx4 levels are lowered, and this led to the development of diabetic kidney disease (DKD) in these patients. 60 Interestingly, reduced Gpx4 levels correlated with an elevation in proteinuria, albumin-to-creatinine ratio, serum creatinine, and sclerosed glomeruli percentage in these diabetic patients. Notably, patients with lower Gpx4 had a higher risk of onset of end-stage kidney disease, compared to diabetic patients with higher Gpx4 levels.…”
Section: Inhibition Of Gpx4mentioning
confidence: 80%
See 2 more Smart Citations
“…24 Wang et al showed that in T2DM patients Gpx4 levels are lowered, and this led to the development of diabetic kidney disease (DKD) in these patients. 60 Interestingly, reduced Gpx4 levels correlated with an elevation in proteinuria, albumin-to-creatinine ratio, serum creatinine, and sclerosed glomeruli percentage in these diabetic patients. Notably, patients with lower Gpx4 had a higher risk of onset of end-stage kidney disease, compared to diabetic patients with higher Gpx4 levels.…”
Section: Inhibition Of Gpx4mentioning
confidence: 80%
“…Notably, patients with lower Gpx4 had a higher risk of onset of end-stage kidney disease, compared to diabetic patients with higher Gpx4 levels. 60 Another study depicts the reduced levels of Gpx4 in kidney biopsy samples of T2DM patients and suggests the role of ferroptosis in kidney tubular cell death in diabetes patients. 24 Moreover, in diabetic mice, the kidney protein levels of both XcT and Gpx4 were markedly reduced, followed by subsequent GSH depletion and lipid ROS-mediated ferroptotic cell death.…”
Section: Inhibition Of Gpx4mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [135] reported on the role of kidney GPx4 expression level in DN progression. The GPx4 expression level was significantly lower in DN patients than in healthy controls and was associated with disease severity and progression [135].…”
Section: Endogenous Antioxidants In Diabetic Nephropathy (Dn)mentioning
confidence: 99%
“…Wang et al [135] reported on the role of kidney GPx4 expression level in DN progression. The GPx4 expression level was significantly lower in DN patients than in healthy controls and was associated with disease severity and progression [135]. Similarly, mice with DN showed significant changes in ferroptosis-associated markers such as increased expression levels of acyl-CoA synthetase long-chain family member 4 (ACSL4) and decreased expression levels of GPx4 [136].…”
Section: Endogenous Antioxidants In Diabetic Nephropathy (Dn)mentioning
confidence: 99%